Effects of Ketamine on Basal Gamma Band Oscillation and Sensory Gating in Prefrontal Cortex of Awake Rats - Qi, Renli (Neurosci Bull, 2018)
Gamma band oscillation (GBO) and sensory gating (SG) are associated with many cognitive functions. Ketamine induces deficits of GBO and SG in the prefrontal cortex (PFC). However, the time-courses of the effects of different doses of ketamine on GBO power and SG are poorly understood. Studies have indicated that GBO power and SG have a common substrate for their generation and abnormalities. In this study, we found that (1) ketamine administration increased GBO power in the PFC in rats differently in the low- and high-dose groups; (2) auditory SG was significantly lower than baseline in the 30 mg/kg and 60 mg/kg groups, but not in the 15 mg/kg and 120 mg/kg groups; and (3) changes in SG and basal GBO power were significantly correlated in awake rats. These results indicate a relationship between mechanisms underlying auditory SG and GBO power. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12264-018-0208-8) contains supplementary material, which is available to authorized users.